A Criminology Of Narrative Fiction - McGregor, Rafe (New horizons in criminology., 2021)
Drawing on complex narratives across film, TV, novels and graphic novels, this authoritative critical analysis demonstrates the value of fictional narratives as a tool for understanding, explaining and reducing crime and social harm. McGregor establishes an original theory of the criminological value of fiction.